Analysis of Cumulative Damage Characteristics of Long Spiral Belled Pile under Horizontal Cyclic Loading at Sea - Haian Liang; Hao Zeng; Kaiwei Cao; Chao Liu; Xinjun Cheng (Shock and Vibration)
In order to study the cumulative damage and failure characteristics of long spiral belled pile under horizontal cyclic loading of offshore wind and waves, a series of indoor experiments on single piles under horizontal cyclic load were carried out. The cycle times as well as load amplitude at the same frequency were considered during the horizontal pseudo-static cyclic tests. On the basis of the distribution of pile deflection, bending moment, and Earth pressure around the pile, the pile-soil interaction was comprehensively discussed. The cumulative energy dissipation characteristics were introduced to describe the damage of test piles. Meanwhile, the effects of load amplitude and cycle times on the cumulative damage of long spiral belled piles were discussed. A power function model for energy dissipation coefficient prediction under multi-stage cyclic load was proposed. The results show that the horizontal peak bearing capacity of long spiral belled pile is increased by 57.2% and 40.4%, respectively, as compared with the straight pile and belled pile under the same conditions. The horizontal displacement mainly occurs at the upper part of the pile. Under the condition of limited cyclic times, the load amplitude has more significant effect on the bearing characteristics of the long spiral belled pile. In contrast to the straight pile and belled pile, the long spiral belled pile has better energy dissipation capacity, and the rank of the energy dissipation capacity of these three piles is long spiral belled pile > belled pile > straight pile. The power function model can well reflect the cumulative damage characteristics of long spiral belled pile under horizontal cyclic loading, and there is a good linear relationship between power function model parameters and load amplitude. The energy dissipation coefficient of long spiral belled pile with diverse cycle times at different mechanical stages of test pile is analysed. Then, the recommended power function model parameters according to different failure stages are proposed. The verification example indicates that the prediction results are close to the measured values with a calculation error of 22%. The prediction model can provide a certain reference for the application of long spiral belled pile in marine structures.